Review of Routine Laboratory Monitoring for Patients with Rheumatoid Arthritis Receiving Biologic or Nonbiologic DMARDs. (31st October 2017) - Rigby, William F. C.; Lampl, Kathy; Low, Jason M.; Furst, Daniel E.
Abstract : Safety concerns associated with many drugs indicated for the treatment of rheumatoid arthritis (RA) can be attenuated by the early identification of toxicity through routine laboratory monitoring; however, a comprehensive review of the recommended monitoring guidelines for the different available RA therapies is currently unavailable. The aim of this review is to summarize the current guidelines for laboratory monitoring in patients with RA and to provide an overview of the laboratory abnormality profiles associated with each drug indicated for RA. Recommendations for the frequency of laboratory monitoring of serum lipids, liver transaminases, serum creatinine, neutrophil counts, and platelet counts in patients with RA were compiled from a literature search for published recommendations and guidelines as well as the prescribing information for each drug. Laboratory abnormality profiles for each drug were compiled from the prescribing information for each drug and a literature search including meta-analyses and primary clinical trials data.